INFLUENCE OF TRAINING ON EMPLOYEES PERFORMANCE IN NGOS: A RESEARCH IN LEBANON - El Musleh, Fatmeh (Atlas Journal, 2021)
This research focuses on the influence of training on employees’ performance (through the ability and desire, discipline and behavior, and the results) in non-governmental organizations (NGOs) in Lebanon. It provides information about the importance of training for employees and their influence on employee performance in NGOs in Lebanon. A quantitative research method of the data collection was adopted using a questionnaire through convenient sampling technique and filled out by 182 respondents. The information and statistical data collected and analyzed using SPSS to test hypotheses and draw conclusions have shown positive signs on the three proposed hypotheses formulated for testing the influence of training on employee performance regarding ability and desire, discipline and behavior, and on the results. The findings and recommendations provide NGOs with the needed knowledge and information on the importance of investing in training to produce a better workforce to better promoting organizational performance. In fact, the findings in this study serve as a guide to students and researchers who want to further research about NGOs in Lebanon to build upon these findings and recommendations to get more insights on the importance of training for employees in NGOs to promote proficiency and effectiveness of staff recruited by NGOs.